Identifikasi Material Tube High Pressure Economizer HRSG Unit 2.3 PLTGU UP Semarang - Eko Sulistiyo; Firman Prasetyo (Sekolah Tinggi Teknik - PLN, 2016)
Heat Recovery Steam Generator (HRSG) is one of the most important equipments in Gas and Steam Power Plants Semarang that have Hp economizer which serves as heater of boiler feed water before it goes to kettle drum and evaporator, so that evaporation process would be more easy with utilizing high temperature exhaust gas from HRSG. But, frequently issue that often arise is shutdown occurrence because of damaged or leaked some tube. It is an issue that has to be solved. In this reaserch, analysis focused to identify material of the unbroken tube to perfome examination of chemical composition of the tube, so the characteristics of the material would be known. The characteristics of material could be known by elements that were contained of that material. From that characteristics, worthiness of the material would be known where the power refers to existing standard and discussion of the reasearh has be supported by a good research meathod